2001
DOI: 10.1007/s003950170066
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias following coronary artery occlusion in rats: is the diabetic heart less or more sensitive to ischaemia?

Abstract: Rhythm disorders are common complications in diabetic patients, due to their enhanced sensitivity to ischaemia. However, experimental studies are inconsistent, and both higher and lower vulnerability to injury has been reported. Our objectives were to compare susceptibility to ventricular arrhythmias in rats with prolonged duration of diabetes induced by streptozotocin (45 mg/kg, i.v.), utilising two different models. Following 8 weeks, either anaesthetised open-chest rats in vivo or isolated Langendorff-perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Long-existing diabetes abrogates preconditioning [16]. Very recently Kristiansen et al [17] showed that both obese and lean type 2 diabetic rats are not protected by preconditioning; however they are less susceptible to ischemia/reperfusion injury.…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…Long-existing diabetes abrogates preconditioning [16]. Very recently Kristiansen et al [17] showed that both obese and lean type 2 diabetic rats are not protected by preconditioning; however they are less susceptible to ischemia/reperfusion injury.…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…The reduction of phospho-hsp27 in correlation to hyperglycemia was effective in abrogating heart tolerance to ischemia in diabetes. Although there is controversy over the effects of hyperglycemia on cardiovascular outcomes, it is important to note that increased tolerance to ischemia is almost exclusively found in type 1 diabetic hearts [8,9,15,16] . In contrast to decreased sensitivity to ischemia of type 1 diabetic hearts, increased sensitivity to myocardial ischemia was found in type 2 diabetic Otsuka Long-Evans Tokushima Fatty rats [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The literature concerning this phenomenon in experimental diabetes studies is ambivalent. Diabetic animals were reported to be either more vulnerable (Bakth et al 1986;Beatch and McNeill 1988;Tosaki et al 1996) or more resistant to ischemia-reperfusion dysrhythmias (Kusama et al 1992;Ravingerova et al 2001;Zhang et al 2002;Knezl at al. 2006;Matejikova et al 2008).…”
Section: Discussionmentioning
confidence: 99%